KEPEMIMPINAN CAMAT DALAM MEMOTIVASI PEGAWAI UNTUK MENINGKATKAN PELAYANAN PUBLIK DI KECAMATAN BUAHBATU KOTA BANDUNG PROVINSI JAWA BARAT - Triyanto Triyanto (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2020)
This study aimed to describe the district leadership in motivating employees to improve service delivery in the District Buahbatu Bandung and describe the factors that inhibit the Head of leadership in motivating employees in the District Buahbatu Bandung and efforts in motivating employees in the District Buahbatu Bandung. Design used in this research is descriptive method with qualitative approach. The data was collected using interview techniques and study documentation. Purposive sample was determined using the technique. The data analysis techniques with interactive models through reduction, presentation of data and draw conclusions. The results of this study indicate that the district leadership in motivating employees to improve service delivery in the district of Buahbatu Bandung good enough in the district where the district leadership Buahbatu transformational leadership style which is characterized by having a clear vision and far-sighted, have charisma, giving motivator and inspiration as well as close to the subordinates. Besides the transactional leadership style district is also evident from the existence of sub-district as a district chief who always give rewards or awards, supervise and control the work and intervene and correction on each activity in proportion and balanced in order to be responsible to the duties and authority vested. Factors that hinder Camat leadership in motivating employees in the district of Buahbatu Bandung the ability of employees; Employee Engagement; Culture and Organizational Structure; Resources and Support, and Employee Behavior Buahbatu district. Efforts are made to motivate employees in the district of Buahbatu Bandung is a: 1) Improve the ability of employees to perform employee development through training techniques and substances in accordance with the needs and demands of work. 2) The need for the involvement of employees in every decision that is taken as a courtesy (respect), 3) Changing the culture of an organization that does not maintain a permanent reference to the applicable rules and regulations in accordance with the hierarchical and organizational structures that exist. 4) Provide support and resources to each activity and program to be and have been implemented; 5) Provide warning and penalties for employees who behave badly as a punishment for any breach of duty; 6) Provide information to employees about the organization’s activities, especially about what to do and how to do it. 7) Provide penalties for employees who are guilty; 8) Establish expectations to employees and understand the feelings that exist within them, to motivate subordinates such as sense of belonging, a sense of participation, a sense of friendship, a sense of welcome in the group, and a sense of achievement. Keywords: Leadership, Motivation and Public Service